Case Report: Pembrolizumab associated lichen planus in early stage triple negative breast cancer - Buyukahisha, Ozge; Ozcelik, Abdullah; Baycelebi, Deniz; Cakir, Asena; Cetin, Bulent (Frontiers in Oncology, 2026)
Triple negative breast cancer (TNBC) is a breast cancer with a poor prognosis, marked by the absence of estrogen (ER) and progesterone (PR) receptors as well as human epidermal growth factor receptor (HER2) expression. Although TNBC is characterized by a high recurrence rate and poorer survival, it is more sensitive to chemotherapy compared to other breast cancer subtypes. The use of targeted immunotherapy approaches has been brought to the agenda for the treatment of both early and advanced TNBC, as TNBCs are immunogenic active tumors. In systemic therapy, addition of immune checkpoint inhibitors to cytotoxic chemotherapy is used as part of the neoadjuvant treatment approach. Pembrolizumab is a monoclonal antibody that blocks the interaction between the programmed death-ligand 1 (PD-L1) receptor on T cells and the PD-L1 and PD-L2 ligands on tumor cells. It has been shown to be effective in TNBC, melanoma, lung cancer and other advanced solid tumors and hematologic malignancies. Several skin-related side effects have been documented, such as pruritus, maculopapular rashes, vitiligo, lichenoid skin reactions, psoriasis, and, in rare cases, severe and potentially life-threatening conditions. We report a rare case of pembrolizumab-associated lichen planus in a 43-year-old woman who received pembrolizumab for neoadjuvant treatment of TNBC.